1995
DOI: 10.1111/j.1749-6632.1995.tb31386.x
|View full text |Cite
|
Sign up to set email alerts
|

Drospirenone: a Novel Progestogen with Antimineralocorticoid and Antiandrogenic Activity

Abstract: Drospirenone (ZK 30595; 6 beta, 7 beta, 15 beta, 16 beta-dimethylen-3-oxo-17 alpha-pregn-4-ene-21, 17-carbolactone) is a novel progestogen under clinical development. Drospirenone is characterized by an innovative pharmacodynamic profile which is very closely related to that of progesterone. Potential applications include oral contraception, hormone replacement therapy and treatment of hormonal disorders. The pharmacological properties of drospirenone were investigated in vitro by receptor binding and transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 22 publications
0
66
0
1
Order By: Relevance
“…Recently, we have demonstrated that Drospirenone (DRSP), a progestogen with a modest antiandrogenic activity, widely used for contraception [7779], strongly inhibits adipose differentiation both in murine (3T3-L1) as well as in human preadipocytes ex vivo . It is important to remark that DRSP is a powerful antagonist of the mineralocorticoid receptor (MR), which is a pivotal factor for the induction of adipogenesis.…”
Section: Effects Of Low Testosterone Levels On Body Fat Massmentioning
confidence: 99%
“…Recently, we have demonstrated that Drospirenone (DRSP), a progestogen with a modest antiandrogenic activity, widely used for contraception [7779], strongly inhibits adipose differentiation both in murine (3T3-L1) as well as in human preadipocytes ex vivo . It is important to remark that DRSP is a powerful antagonist of the mineralocorticoid receptor (MR), which is a pivotal factor for the induction of adipogenesis.…”
Section: Effects Of Low Testosterone Levels On Body Fat Massmentioning
confidence: 99%
“…Drospirenone is a fourth generation OC and it possesses antimineralocorticoid effects not present in previous generations of OCs. Its antimineralocorticoid potency is approximately eight times greater than spironolactone [3], thus a 3 mg tablet of drospirenone has a similar effect to 20-25 mg of spironolactone [4]. This activity enhances sodium, chloride, and water excretion, while reducing the excretion of potassium, ammonium, and phosphate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DRSP differs from most synthetic progestogens as it demonstrates a similar pharmacological profile to endogenous progestogens [345]. Consequently, DRSP is devoid of any estrogenic, glucocorticoid or anti-glucocorticoid activity but exhibits anti-aldosterone and anti-androgenic properties.…”
Section: Introductionmentioning
confidence: 99%